Badan Bank Tanah Indonesia dengan Land Bank Agency Belanda: Studi Komparasi - Susantio, Catherine; Beatrice, Marvella (Universitas Ekasakti, 2024)
This research aims to conduct a comparative study between the Indonesian Land Bank Agency and the Land Bank Agency in the Netherlands. The focus of the study is to analyze the structure, functions, and performance impact of both institutions in supporting land asset management. The research method involves a comparative analysis, incorporating literature review, interviews, and collection of secondary data related to the policies, strategies, and implementation of these institutions. The results of this research are expected to provide a deeper understanding of the roles of the Indonesian Land Bank Agency and the Land Bank Agency in the Netherlands in land asset management and their contributions to sustainable development.